Сomparative Analysis of Postoperative Pain Syndrome in Cardioesophageal Cancer - Yakhyo Sheraliyevich Khakimov; Abrorjon Ahmadjonovich Yusupbekov; Gafur Normurodovich Saidov; Elyor Ergashboevich Juraev; Bekzod Boymatovich Usmonov; Otabek Dilshodovich Tuychiev (American Journal of Biomedicine and Pharmacy, 2026)
Postoperative pain syndrome (POPS) remains a significant clinical challenge in patients undergoing surgery for cardioesophageal cancer (CEC). Despite the implementation of multimodal analgesia protocols, adequate pain control is not consistently achieved. This study aimed to comparatively assess postoperative pain intensity depending on the type of surgical access and tumor characteristics in patients with CEC. Eighty-five patients who underwent open surgical treatment were evaluated using the Numeric Rating Scale (NRS). Pain intensity was analyzed in relation to surgical approach, tumor phenotype, disease stage, and demographic factors. The highest pain intensity was observed in patients who underwent thoracophrenicolaparotomy. Multimodal analgesia improved pain control; however, pain levels exceeded the adequate analgesia threshold (>4 points) in a substantial proportion of patients. The findings indicate that postoperative pain intensity is primarily associated with the extent of surgical trauma rather than gender or age factors, highlighting the need for optimization of regional analgesia techniques in oncologic surgery.